Evidence of enhanced magnetism in cool, polluted white dwarfs - Kawka, Adela; Vennes, S.; Ferrario, L.; Paunzen, E. (OXFORD UNIV PRESS, 2019)
We report the discovery of a new, polluted, magnetic white dwarf in the Luyten survey of high-proper motion stars. High-dispersion spectra of NLTT 7547 reveal a complex heavy element line spectrum in a cool (≈5200 K) hydrogen-dominated atmosphere showing the effect of a surface averaged field of 163 kG, consistent with a 240 kG centred dipole, although the actual field structure remains uncertain. The abundance pattern shows the effect of accreted material with a distinct magnesium-rich flavour. Combined with earlier identifications, this discovery supports a correlation between the incidence of magnetism in cool white dwarfs and their contamination by heavy elements.